Yersinia protein kinase A phosphorylates vasodilator‐stimulated phosphoprotein to modify the host cytoskeleton. (22nd November 2014) - Ke, Yuehua; Tan, Yafang; Wei, Na; Yang, Fen; Yang, Huiying; Cao, Shiyang; Wang, Xiaohui; Wang, Jian; Han, Yanping; Bi, Yujing; Cui, Yujun; Yan, Yanfeng; et al.
Summary Pathogenic Yersinia species evolved a type III secretion system that injects a set of effectors into the host cell cytosol to promote infection. One of these effectors, Yersinia protein kinase A (YpkA), is a multidomain effector that harbours a Ser/Thr kinase domain and a guanine dissociation inhibitor (GDI) domain. The intercellular targets of the kinase and GDI domains of YpkA were identified to be Gαq and the small GTPases RhoA and Rac1, respectively, which synergistically induce cytotoxic effects on infected cells. In this study, we demonstrate that vasodilator‐stimulated phosphoprotein (VASP), which is critical for regulation of actin assembly, cell adhesion and motility, is a direct substrate of YpkA kinase activity. Ectopic co‐expression of YpkA and VASP in HEK293T cells leads to the phosphorylation of VASP at S157, and YpkA kinase activity is essential for VASP phosphorylation at this site. Moreover, YpkA directly phosphorylates VASP in in vitro kinase assay. YpkA‐mediated VASP phosphorylation significantly inhibits actin polymerization and promotes the disruption of actin cytoskeleton, which inhibits the phagocytosis. Taken together, our study found a novel molecular mechanism used by YpkA to disrupt cytoskeleton dynamics, thereby promoting the anti‐phagocytosis ability of pathogenic Yersiniae.